The influence of boron carbide clad with a nickel-based alloy on the abrasive wear rate of aromatic polyamide phenylon - Yeromina, K.A.; Tomina А.-М.V.; Yarovyi, Ya.E. (Problems of Tribology, 2024)
The paper presents the results of the development of new composite materials based on aromatic polyamide phenylon, filled with dispersed boron carbide and clad with PKHN-15 alloy. The influence of the percentage content of the filler on the abrasion rate under the conditions of friction with rigidly fixed abrasive particles was studied. It is shown that the degree of filling determines the rate of abrasive wear of composites, which reaches a minimum at a filler content of 25 wt.%. The introduction of boron carbide clad with the PKHN-15 alloy leads to a decrease in the abrasion rate of the aromatic polyamide phenylon by 6.2-9 times, which correlates with the strength indicators. The roughness of the composites is almost at the same level, from which we can conclude that the amount of filler affects their wear mechanism. An increase in microhardness at the boundary of the "polymer-filler" separation was noted, which may indicate the presence of interaction between the polymer and the filler. It is shown that the abrasive wear rate for composites containing 10-15 wt.% filler is more stable than for composites with a larger amount of filler. Developed composites are recommended for work in friction units operating in abrasive conditions, or as working bodies of grain harvesting machines and mechanisms that are in constant contact with grain which acts as an abrasive for working surfaces.